2020
DOI: 10.1177/0964528420960479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcutaneous electrical acupuncture point stimulation on peripheral capillary oxygen saturation in elderly patients undergoing colonoscopy with sedation: a prospective randomized controlled trial

Abstract: Introduction: This study investigated whether transcutaneous electrical acupuncture point stimulation (TEAS) at PC6 can reduce the proportion of elderly patients experiencing a drop of ⩾4% in peripheral capillary oxygen saturation (SpO2) while undergoing colonoscopy under sedation. Methods: A total of 32 elderly patients (aged ⩾ 65 years) scheduled for colonoscopy were randomly assigned in a 1:1 ratio to receive either real or sham TEAS (treatment or control groups, respectively). Each patient received oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…. The heterogeneity of the two treatment methods in the included articles [14][15][16][17][18][19][20][21][22][23][24][25] was evaluated, and the results showed that there was no heterogeneity among these articles in terms of neurological recovery (I 2 = 0:00%). There were no heterogeneity among the included articles in motor function (I 2 = 0:00%) and no heterogeneity among articles in functional recovery (I 2 = 0:00%).…”
Section: Heterogeneity Assessment Resultsmentioning
confidence: 99%
“…. The heterogeneity of the two treatment methods in the included articles [14][15][16][17][18][19][20][21][22][23][24][25] was evaluated, and the results showed that there was no heterogeneity among these articles in terms of neurological recovery (I 2 = 0:00%). There were no heterogeneity among the included articles in motor function (I 2 = 0:00%) and no heterogeneity among articles in functional recovery (I 2 = 0:00%).…”
Section: Heterogeneity Assessment Resultsmentioning
confidence: 99%
“…Full-text screening of the remaining 36 articles was performed, resulting in eight articles being selected for inclusion in the metaanalysis (Fig. 1) [13][14][15][16][22][23][24][25]. The j value was 0.87, indicating a high degree of agreement between the two reviewers.…”
Section: Search Resultsmentioning
confidence: 99%
“…Interventions in the treatment groups included acupuncture [22][23][24][25], EA [13,16], and TEAS [14,15]. Interventions in the control groups included SA [13,22,25], PA [13], sham TEAS [14,15], no acupuncture [22][23][24][25], and no EA [16]. Six of the studies had Jadad scores C 3 [13][14][15][22][23][24].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations